2008
DOI: 10.1093/molbev/msn288
|View full text |Cite
|
Sign up to set email alerts
|

The Single Mitochondrial Porin of Trypanosoma brucei is the Main Metabolite Transporter in the Outer Mitochondrial Membrane

Abstract: All mitochondria have integral outer membrane proteins with beta-barrel structures including the conserved metabolite transporter VDAC (voltage dependent anion channel) and the conserved protein import channel Tom40. Bioinformatic searches of the Trypanosoma brucei genome for either VDAC or Tom40 identified a single open reading frame, with sequence analysis suggesting that VDACs and Tom40s are ancestrally related and should be grouped into the same protein family: the mitochondrial porins. The single T. bruce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
87
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 37 publications
7
87
0
1
Order By: Relevance
“…Characterizing protein-import machinery in phylogenetically diverse Euglenozoa would test this and whether its greater simplicity in trypanosomes (and I suggest all Euglenozoa) is primitive. On VDAC/Tom40 mitochondrial porin trees, the root of the VDAC half is precisely between Euglenozoa and neokaryotes (Pusnik et al 2009), as in my hypothesis.…”
Section: Where Is the Eukaryotic Root?mentioning
confidence: 61%
“…Characterizing protein-import machinery in phylogenetically diverse Euglenozoa would test this and whether its greater simplicity in trypanosomes (and I suggest all Euglenozoa) is primitive. On VDAC/Tom40 mitochondrial porin trees, the root of the VDAC half is precisely between Euglenozoa and neokaryotes (Pusnik et al 2009), as in my hypothesis.…”
Section: Where Is the Eukaryotic Root?mentioning
confidence: 61%
“…These are the ortholog of Sam50, a member of the Omp85 family, and four β-barrel proteins from the general mitochondrial porin superfamily. One of these is the T. brucei VDAC, functioning as a metabolite transporter (23). A second one is the protein import pore ATOM, whose evolutionary origin is controversial, but shows at least some similarity to the mitochondrial porin family (24,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas VDAC and Tom40 have so far been found in all eukaryotes, including T. brucei (23,24), MDM10 is specific to the fungal clade.…”
Section: Significancementioning
confidence: 97%
“…These results clearly indicate that TbPorin is critical for mitochondrial activities thus required for normal cell growth in both forms. Recently, Pusnik et al reported that depletion of the VDAC affects cell growth of the procyclic form only in the absence of glucose (35). Their double-knockout cell lines grew similarly to controls in regular procyclic medium SDM-79.…”
Section: Brucei Vdac Is Critical For Mitochondrial Activity 1421mentioning
confidence: 99%